2021
DOI: 10.1021/acs.iecr.1c01169
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reduction and Crystallization Hybrid System for Removal and Recovery of Lead (Pb)

Abstract: The heavy metal lead (Pb) is toxic to humans, animals, and plants and shows persistence and is nondegradable in aquatic media. A novel method has been proposed using photocatalysis (PC) and reduction crystallization (RC) for efficient removal and recovery of lead (Pb) from the aqueous phase. Using photocatalysis, maximum removal of lead ions (Pb 2+ ) was 79.6% under optimized conditions (2 g L −1 TiO 2 , pH 5.3, and 35 W cm −2 UV light intensity). However, reduction crystallization removed 90% lead ions (Pb 2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…An intimately linked photocatalysis and biodegradation (ICPB) system comprised of Fe 3+ /g-C 3 N 4 and biofilm were developed for the treatment of synthetic household wastewater containing SMX. Qidi Liu Jun Hou (Kumar et al 2020) was the researcher in this study. The results showed that this ICPB system could remove 96.27% of SMX and 86.57% of COD simultaneously, which was superior to photocatalysis alone (SMX 100%, COD 4.2%) and solo biodegradation (SMX 42.21%, COD 95.1%).…”
Section: An Overview Of Photocatalyst Applications In Wastewater Trea...mentioning
confidence: 99%
“…An intimately linked photocatalysis and biodegradation (ICPB) system comprised of Fe 3+ /g-C 3 N 4 and biofilm were developed for the treatment of synthetic household wastewater containing SMX. Qidi Liu Jun Hou (Kumar et al 2020) was the researcher in this study. The results showed that this ICPB system could remove 96.27% of SMX and 86.57% of COD simultaneously, which was superior to photocatalysis alone (SMX 100%, COD 4.2%) and solo biodegradation (SMX 42.21%, COD 95.1%).…”
Section: An Overview Of Photocatalyst Applications In Wastewater Trea...mentioning
confidence: 99%
“…Lead is the most toxic metal, often considered a primary pollutant. The presence of this metal in water bodies mainly relies on different processing industries, such as the battery industry, antiknocking agent-tetraethyl-lead manufacturing, metal plating and finishing industry, and ceramic/glass industry [84]. Lead accumulation in the human body, beyond its permissible limit (0.05 mg/L), can create several diseases anemia, kidney malfunction, brain tissue damage, and death in severe cases.…”
Section: Lead (Pb)mentioning
confidence: 99%
“…Con este volumen, el costo total de fabricación fue de 2,8 M$/año con un costo de producción de $127 por unidad. Asimismo, Kumar et al, (2021) aplicaron un sistema híbrido de reducción y cristalización fotocatalítica para la eliminación y recuperación de plomo. Los resultados demostraron que, usando fotocatálisis, la eliminación máxima de iones de plomo fue del 79.6% en condiciones optimizadas con dosis de 2 g/L TiO2, pH 5.3 y 35 W/cm 2 de intensidad de luz UV, mientras que la cristalización por reducción eliminó el 90% de los iones de plomo utilizando hidrato de hidracina como agente reductor con parámetros optimizados de pH 10 y temperatura a 80 °C.…”
Section: Introductionunclassified